Implementation of Aceh Qanun Number 11 of 2013 in Handling Beggars in Banda Sakti District, Lhokseumawe City - Erika Yuningsih; Ti Aisyah; Murniati; Muhammad Hasyem; Maisyura (PT PUSTAKA CENDEKIA GROUP, 2024)
Implementation of Aceh Qanun Number 11 of 2013 in Handling Beggars in Banda Sakti District, Lhokseumawe City is one of the efforts in handling the problem of beggars. This study aims to determine how the implementation of Aceh Qanun Number 11 of 2013 in handling beggars in Banda Sakti District, Lhokseumawe City and to find out what are the obstacles to the implementation of Aceh Qanun Number 11 of 2013 in Banda Sakti District, Lhokseumawe City has not been running effectively. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews and documentation. The results of this study are that the implementation of Aceh Qanun Number 11 of 2013 in handling beggars in Banda Sakti District, Lhokseumawe City has not been running effectively, because the Social Service has not implemented the provision of training services, employment opportunities and business opportunities for beggars. This is because there is no budget and special facilities to handle beggars, lack of funding sources, human resources and infrastructure resources to support the implementation of education and training services as well as employment and business opportunities for beggars. Communication between agencies is also one of the obstacles to the implementation of Aceh Qanun Number 11 of 2013 in handling beggars in Banda Sakti District, Lhokseumawe City. The social service can provide education and training services to beggars as well as employment and business opportunities. The social service can also establish relationships with other agencies in the context of implementing Aceh Qanun Number 11 of 2013 with other agencies such as BLK and DISPERINDAGKOP.